Usefulness of comprehensive income reporting for dividend policy in the polish listed companies - Aleksandra Pieloch-Babiarz; Artur Sajnóg (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
This study examines the strength and character of relationship between dividend policy and comprehensive income in Polish manufacturing companies. We formulated two research questions: 1) does comprehensive income determine the ability to pay out a dividend? 2) what is the key role of comprehensive income in shaping a dividend policy? To receive the answers to these questions, we put a research hypothesis stating that in the Polish listed companies a positive relationship between comprehensive income and dividend policy can be observed. The research was conducted among the companies operating in the manufacturing sector (4xx of the Warsaw Stock Exchange (the WSE) classification). The analytical period is between 2009–2017 and reflects the current legal status of the financial reporting of public companies in Poland. Finally, our analysis comprised 83 manufacturing companies and 664 observations. The study procedure was carried out in two stages. The first stage was to show the results of empirical research conducted among the analysed companies and regarding the variability of comprehensive income in comparison to net income (consequently other comprehensive income). At the second stage, we presented the results of investigation on the strength and character of an impact of comprehensive income on dividends. For that purpose, two research methods were used. Firstly, we calculated the Pearson’s correlation coefficients between comprehensive income (and net income) and future dividend ratios, as well as the other company’s performance and tested for significance using the t-Student test. Secondly, we used regression analysis and two one-equation models built for comprehensive income and net income. Moreover, we used descriptive statistics, t- Student test, and F-test. The conducted research allowed us to draw two main conclusions: 1) there was a positive character of dependence between comprehensive income and future dividend, however, the correlation between them was very weak; 2) the impact of comprehensive income on future dividend ratio was positive, but we noted no statistical significance.